UJI EFEKTIFITAS Trichoderma harzianum DENGAN FORMULASI GRANULAR RAGI UNTUK MENGENDALIKAN PENYAKIT JAMUR AKAR PUTIH (Rigidoporus microporus (Swartz:fr.) van Ov) PADA TANAMAN KARET DI PEMBIBITAN - Marah Halim Pulungan; Lahmuddin Lubis; Fatimah Zahara; Zaida Fairuzah (Universitas Sumatera Utara, 2014)
ABSTRACTResearch on title testing the effectiveness of Trichoderma harzianum yeast granular formulations tocontrol white root fungus disease (Rigidoporus microporus (Swartz:fr.) van Ov) in the rubber plantnurseries. Required more efficient technologies in utilizing Trichoderma spp, one of which is makeformulations in granular form. Granular formulations easier in application, longer storage period andsupport the deployment of Trichoderma in the soil. This study aims to know the effectiveness ofT. harzianum granular formulations with a variety of mixed media in controlling white root diseasefungus in rubber plant. The research was conducted at Rubber Research Institute of Plant Sungei Putih,Deli Serdang, North Sumatra from Desember 2012-April 2013. The method used randomized blockdesign (RBD) Non Factorial consists of 10 treatments with three replications. The results showed thatthe highest disease intensity at treatment control (83.33%) and the lowest at treatment rice flour +T.harizianum (05.55%). High rubber stump buds highest at treatment rice flour + sugar + bread yeast +T. harzianum (24.44 cm) and the lowest at treatment control (7.78 cm). While soil pH was highest attreatment rice flour + tape yeast + T. harzianum ground limestone (6.33), and the lowest soil pH ontreatment rice flour + tape yeast + sulfur + T. harzianum (4.33). Growth and the antagonist ofT. harzianum higher compared with the addition of other fungi that could be a competitor for space andnutrients of T. harzianum.Keywords : Trichoderma harzianum, yeast, granular, rubber, Rigidoporus microporus